Caracterização genética de acessos de egéria (Egeria spp.) coletados no estado de São Paulo utilizando RAPD - Martins, D. [UNESP] (2003)
The aim of this research was to study the genetic variability of egeria (Egeria spp.) accesses, sampled in seven reservoirs throughout the state of São Paulo. The RAPD (Random Amplified Polymorphic DNA) analysis was used, with six primers (X03, Y09, Y11, Z11, Z12 and W06) furnishing 23 polymorphic loci for Egeria densa. The plants from the Avanhandava and Promissão reservoirs showed the greatest genetic similarity, since both are located on the Tietê river. The Salto Grande and Promissão reservoirs presented plants with the greatest genetic distance (0.1792). For the Egeria najas species, 52 polymorphic loci were analyzed and nine primers (X01, X02, X03, X05, X09, X10, X11, Z11 and Z13) were selected. The greatest genetic distance verified was 0.2791, between the Ibitinga and Jupiá reservoir samples, caused by the long geographic distance between them.